2018
DOI: 10.1038/s41598-018-32149-z
|View full text |Cite
|
Sign up to set email alerts
|

Origin of relationship between ferromagnetic response and damage in stretched systems

Abstract: This article presents a study whose purpose is to elucidate the damage effects in thin films on their magnetic response. Co40Fe40B20 and Ni80Fe20 films of different nanometric thicknesses were stretched by more than 10% and in situ probed by atomic force microscopy measurements to determine their irreversible mechanical behavior (multi-cracking, buckling). Once these phenomena have been well identified, magnetic behavior of these stretched systems has been studied by ferromagnetic resonance to measure resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Merabtine et al have shown that the magnetic properties of a CoFeB film deposited on Kapton modified due to the high stress applied during the damage formation (cracking/buckling). But there is almost no effect of cracking or buckling on the magnetic properties of zero magnetostrictive alloy NiFe [37]. Hence we can conclude that the negligible effect of compression is not a result of structural modification of our film.…”
Section: Bubble Domainmentioning
confidence: 64%
“…Merabtine et al have shown that the magnetic properties of a CoFeB film deposited on Kapton modified due to the high stress applied during the damage formation (cracking/buckling). But there is almost no effect of cracking or buckling on the magnetic properties of zero magnetostrictive alloy NiFe [37]. Hence we can conclude that the negligible effect of compression is not a result of structural modification of our film.…”
Section: Bubble Domainmentioning
confidence: 64%
“…Several factors influence the damping of FMR, having an internal and external character. The internal contributions are related to the properties of a given material [ 2 , 7 , 20 ] (i.e., the effect of eddy current damping), while the external ones are associated with defects in the sample [ 20 , 25 , 26 , 27 ]. In polycrystalline materials, the line broadening mechanism can be dominated by magnetocrystalline anisotropy (in conjunction with polycrystalline structure) [ 19 , 21 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the above-mentioned factors, the FMR absorption characteristic can provide information about the state of the material, as deformations in steels significantly affect changes in their structure and properties. Growing strains increase the number of defects in the lattice, which cause the broadening of the absorption line [ 25 , 28 ]. In the case of polycrystals, grain boundaries are an additional influencing element.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations